First description of Nodding Syndrome in the Central African Republic. - Salvatore Metanmo; Farid Boumédiène; Pierre-Marie Preux; Robert Colebunders; Joseph N Siewe Fodjo; Eric de Smet; Emmanuel Yangatimbi; Andrea S Winkler; Pascal Mbelesso; Daniel Ajzenberg (Public Library of Science (PLoS), 2021)
Background The term Nodding Syndrome (NS) refers to an atypical and severe form of childhood epilepsy characterized by a repetitive head nodding (HN). The disease has been for a long time limited to East Africa, and the cause is still unknown. The objective of this study was to confirm the existence of NS cases in Central African Republic (CAR). Methodology/principal findings This was a cross-sectional descriptive study in the general population. The identification of NS cases was conducted through a door-to-door survey in a village near Bangui along the Ubangui River. Based on Winkler's 2008 and the World Health Organization (WHO)'s 2012 classifications, the confirmation of cases was done by a neurologist who also performed the electroencephalograms. No laboratory tests were done during this investigation. Treatment was offered to all patients. A total of 6,175 individuals was surveyed in 799 households. After reviewing the cases, we identified 5 NS cases in girls aged between 8 and 16. The age of onset of the seizures was between 5 and 12 years of age. Two cases were classified as "HN plus" according to Winkler's 2008 classification. Four NS cases were classified as probable and one as confirmed according to the WHO's 2012 classification. Three of them presented with developmental delay and cognitive decline, and one had an abnormally low height-for-age z-score. Electroencephalographic abnormalities were found in four patients. Conclusions/significance Nodding Syndrome cases were described in CAR for the first time. Despite certain peculiarities, these cases are similar to those described elsewhere. Given that only a small part of the affected area was investigated, the study area along the Ubangui River needs to be expanded in order to investigate the association between Onchocerca volvulus and NS and also evaluate the real burden of NS in CAR.